I Wish I Could Believe - Day Lewis, C. (Cecil) (Tufts Archival Research Center, 2006)
Cecil Day Lewis, Chair of Poetry at Oxford University, describes faith as the core of an individual's being, and states his faith (defined thusly) as the creation of poems.